Explaining the Adoption Gap in Digital Learning Platforms: The Role of Task-Technology Fit, Performance Expectancy, and Trust - Irfan Sholeh; Muhammad Awaluddin (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
Tempo Institute is a digital learning platform in Indonesia that is facing the challenge that most registered users do not convert into active users. The gap between registered users and active users in this study is referred to as the adoption gap. This study aims to analyze the adoption gap at Tempo Institute by testing an integrated model that combines UTAUT2, Task-Technology Fit (TTF), and Trust. Data were collected from 400 registered users using PLS-SEM techniques to interpret and analyze the data assisted by SmartPLS 4 software. Based on the analysis of this study, Performance Expectancy is the strongest driver of user registration intention, followed by Trust and Task-Technology Fit. But, these three factors have limitations in maintaining long-term active users. Habits and Enabling Conditions are factors that determine whether users remain active on the platform. The main theoretical contribution of this study is the TTF-UTAUT2 Trust Acquisition-Retention Duality Framework, which proposes that the factors that motivate someone to register on a digital learning platform are fundamentally different from the factors that keep them actively using the platform. The differences are important to understand and close the adoption gap in digital learning platforms, especially at Tempo Institute.